2004
DOI: 10.1073/pnas.0308249101
|View full text |Cite
|
Sign up to set email alerts
|

Short amino acid stretches can mediate amyloid formation in globular proteins: The Src homology 3 (SH3) case

Abstract: Protein misfolding and deposition underlie an increasing number of debilitating human disorders. We have shown that model proteins unrelated to disease, such as the Src homology 3 (SH3) domain of the p58␣ subunit of bovine phosphatidyl-inositol-3-kinase (PI3-SH3), can be converted in vitro into assemblies with structural and cytotoxic properties similar to those of pathological aggregates. By contrast, homologous proteins, such as ␣-spectrin-SH3, lack the capability of forming amyloid fibrils at a measurable r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
194
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 236 publications
(209 citation statements)
references
References 63 publications
11
194
0
1
Order By: Relevance
“…Work on a homologous protein of the PI3-SH3 domain, the ␣-spectrin SH3 domain, and several PI3-SH3 mutants has suggested that residues located in part of the RT loop and adjacent divergent turn (DT) in the native state, act as ''mediators'' or ''facilitators'' in the conversion of the soluble PI3-SH3 into amyloid fibrils (22). Other studies using molecular dynamics simulations to probe aggregation of the Src-SH3 domain concluded that the RT loop sequence constitutes the initial core structure for fibril formation (23).…”
Section: Discussionmentioning
confidence: 99%
“…Work on a homologous protein of the PI3-SH3 domain, the ␣-spectrin SH3 domain, and several PI3-SH3 mutants has suggested that residues located in part of the RT loop and adjacent divergent turn (DT) in the native state, act as ''mediators'' or ''facilitators'' in the conversion of the soluble PI3-SH3 into amyloid fibrils (22). Other studies using molecular dynamics simulations to probe aggregation of the Src-SH3 domain concluded that the RT loop sequence constitutes the initial core structure for fibril formation (23).…”
Section: Discussionmentioning
confidence: 99%
“…45 Investigations into the effect of mutations altering the charge state of a protein without altering its hydrophobicity or secondary structural propensity showed that aggregation was favoured by those mutations which brought about a reduction in the net charge. 11,46,47 Similarly, in vivo experiments have shown that mutations decreasing the positive charge on a molecule increase the aggregation propensity and mutations increasing the net charge result in decreased aggregation. 48 Amyloidogenic proteins which are predominantly a-helical, must undergo an a-helix to b-sheet conversion during the formation of amyloid fibrils.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,[8][9][10] In some cases, the aggregates formed from these nondisease-associated proteins have been shown to have cytotoxic properties similar to those of pathological aggregates. 11 A diverse group of proteins has been observed to form amyloid-like fibrils having specific physiological functions in nonpathological conditions in a wide range of organisms, such as proteins of the eggshell chorion in the silk moth, spidroin in the spider, Pmel17, which plays a central amyloid has been dubbed functional amyloid to distinguish it from the amyloid associated with disease conditions, but from a structural point of view both types of amyloid are the same. 16,17 The definitive characteristic of amyloid fibrils formed in all the aforementioned cases is the socalled ''cross-b'' structure as revealed by X-ray diffraction, in which the polypeptide chain is organised into b-sheets arranged parallel to the longitudinal fibril axis, with constituent b-strands perpendicular to the fibril axis.…”
Section: Introductionmentioning
confidence: 99%
“…The sequence determinant of amyloid formation has been studied with various experi-mental [16][17][18][19][20][21][22] and theoretical [23][24][25][26] approaches. It has been shown that the overall hydropho-bicity 18 and net charge 20 of a peptide, to some extent, may impact the aggregation rate.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the overall hydropho-bicity 18 and net charge 20 of a peptide, to some extent, may impact the aggregation rate. There are increasing evidence that the capability of a protein to form amyloids strongly depends on certain short amino acid stretches in the sequence [17][18][19] . To support a proteome-wide search for aggregation-prone peptide segments, a number of predictors have been made available [27][28][29] .…”
Section: Introductionmentioning
confidence: 99%